Receptor activity modifying proteins (RAMPs) interact with the VPAC2 receptor and CRF1 receptors and modulate their function. (24th January 2013) - Wootten, D; Lindmark, H; Kadmiel, M; Willcockson, H; Caron, KM; Barwell, J; Drmota, T; Poyner, DR
Abstract : Background and Purpose: Although it is established that the receptor activity modifying proteins (RAMPs) can interact with a number of GPCRs, little is known about the consequences of these interactions. Here the interaction of RAMPs with the glucagon‐like peptide 1 receptor (GLP‐1 receptor), the human vasoactive intestinal polypeptide/pituitary AC‐activating peptide 2 receptor (VPAC2 ) and the type 1 corticotrophin releasing factor receptor (CRF1 ) has been examined. Experimental Approach: GPCRs were co‐transfected with RAMPs in HEK 293S and CHO‐K1 cells. Cell surface expression of RAMPs and GPCRs was examined byelisa . Where there was evidence for interactions, agonist‐stimulated cAMP production, Ca 2+ mobilization and GTPγS binding to Gs, Gi, G12 and Gq were examined. The ability of CRF to stimulate adrenal corticotrophic hormone release in R amp2 +/– mice was assessed. Key Results: The GLP‐1 receptor failed to enhance the cell surface expression of any RAMP. VPAC2 enhanced the cell surface expression of all three RAMPs. CRF1 enhanced the cell surface expression of RAMP2; the cell surface expression of CRF1 was also increased. There was no effect on agonist‐stimulated cAMP production. However, there was enhanced G‐protein coupling in a receptor and agonist‐dependent manner. The CRF1  : RAMP2 complex resulted in enhanced elevation of intracellular calcium to CRF and urocortin 1 but not sauvagine. In R amp2 +/– mice, there was a loss of responsiveness to CRF. Conclusions and Implications: The VPAC2 and CRF1 receptors interact with RAMPs. This modulates G‐protein coupling in an agonist‐specific manner. For CRF1, coupling to RAMP2 may be of physiological significance.